The Orthoptera of Hatay Province, S. Turkey. - Naskrecki, Piotr; Ünal, Mustafa (Contributions to Entomology = Beiträge zur Entomologie, 1995)
A full list of Orthoptera recorded from Hatay province in S. Turkey is given. Two species, Leptophyes karanae sp. n. and Isophya splendida sp. n., are described as new; two species, Morphacris fasciata (Thungb.) and Conocephalus kisis gaukleri Harz are recorded from Turkey for the first time, and eight additional species are new to the province.Nomenclatural Actssplendida Naskrecki & Ünal, 1995 (Isophya), spec. n.karanae Naskrecki & Ünal, 1995 (Leptophyes), spec. n.